Penyuluhan dalam Upaya Peningkatan Kesadaran Pengelolaan Limbah Pabrik Mie Rumahan Kota Kendari - Karimuna, Siti Rabbani; Abidah, Husna; Lestari, Dita; Anggraeni, Evitri; Yani, Indra; Indah, Lidya Sri Ratu; Astuti, Lutfia Andi; Faturrahman, Muh. Ekzah; Sulistiawati, Naqiyyah Aulia; Ferlian, Nesti; Nirmala, Nirmala; Salam, Nur Aprilia Mutiara; Ramadani, Rahma; Tambunan, Renike; Wahyudi, Rizat; Hasana , Uswatul (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2025)
Improper waste management, especially in home industries such as noodle factories, can cause environmental pollution and public health problems. This community service activity aims to increase awareness of waste management in home noodle factories in Baruga District, Kendari City, Southeast Sulawesi. The methods used in this activity are interviews, direct observation, education using poster media, and qualitative evaluation. The results of the observation show that the noodle factory already has a Wastewater Treatment Plant (IPAL) and Wastewater Drainage Channel (SPAL), but the management of liquid waste is still not optimal because the disposal of liquid waste is still allowed to stagnate around the factory area. In contrast, solid waste such as noodle crumbs and recycled waste (plastic, sacks, used egg racks) have been managed well; noodle crumbs are given to farmers as animal feed and recycled waste is given to used goods collectors. The conclusion of this activity shows that solid waste management in noodle factories has been running quite effectively, but liquid waste management still needs to be improved so as not to pollute the environment.